Extraction of steviol glycosides from Stevia rebaudiana (Bertoni) leaves by high‐speed shear homogenization extraction. Issue 12 (9th October 2019) - Xu, Shaohe; Wang, Guanyu; Guo, Ruili; Wei, Zhong; Zhang, Jinli
Abstract: An efficient high‐speed shear homogenization extraction (HSHE) technique was employed for extracting stevioside (STV) and rebaudioside A (RA) from Stevia rebaudiana (Bertoni) leaves. The HSHE extraction procedure was optimized and compared with other conventional extraction techniques. HSHE showed a better extraction efficiency than solvent extraction (SE), ultrasound‐assisted extraction (UAE), and microwave‐assisted extraction (MAE) methods. Based on single‐factor experiments, the extraction conditions of HSHE method were optimized by response surface method (RSM) modeling. The optimal conditions were 59% ethanol aqueous solution as extraction agent, 8 min extraction time, and 68°C extraction temperature. The yields of STV, RA, and rebaudioside C (RC) were 5.37 ± 0.10%, 8.68 ± 0.13%, and 0.99 ± 0.03%, respectively. In addition, the contents of other components in crude extract, such as pigments, proteins, and pectin, extracted by HSHE, were compared with SE, UAE, and MAE methods. The result showed that the HSHE method has the advantages of low extraction temperature, high efficiency, and low time and energy consumption. The study demonstrated that HSHE has a great potential for the extraction of steviol glycosides from S. rebaudiana (Bertoni) leaves. Practical applications: Steviol glycosides (SGs) are a new natural sweetener with high safety, good stability, and nonfermentation, which is herbal plant of the composite extracted from S. rebaudiana (Bertoni). It has the characteristics of high sweetness and low thermal energy. Its safety has been approved by the European Food Safety Administration (EFSA) and Joint Committee of Experts on Food Additives (JECFA). Generally speaking, SG is extracted from S. rebaudiana (Bertoni) by SE, UAE, and MAE methods. However, these methods have the disadvantages of low efficiency, low yield, and high solvent consumption. At present, there is no literature reported on the extraction of SG from S. rebaudiana (Bertoni) by HSHE method. Therefore, this study is to optimize the extraction process of HSHE and compare the contents of impurities in the crude extracts of different extraction methods, in order to provide a new method for extraction of SG from S. rebaudiana (Bertoni).